UNDERGRADUATE AGRICULTURE EDUCATION IN NEPAL: A COMPREHENSIVE REVIEW - Maharjan, Salina; Dhakal, Tikaram (International Journal of Research -GRANTHAALAYAH, 2023)
Higher education is perceived as a capital outlay and a potential transformer of the socio-economic and cultural development of a nation. Nepal has a very brief history of modern educational systems which traces back to 1959 when Tribhuvan University was established as the first university in the country. Though the formal education in agriculture began in 1968 with the upgrade of the School of Agriculture into the College of Agriculture launching a two-year Intermediate of Science in Agriculture program, the institutes offering the undergraduate-level Bachelor of Science in Agriculture are recorded to stretch out only after the 1990s. The trend of establishment of undergraduate agricultural colleges has faced many ups and downs but the highest number of agricultural colleges were found to be established in the year 2018 i.e., 10. In the current situation, seven universities and their thirty-three constituent and affiliated colleges are offering bachelor’s degree in agriculture. Regardless of the ample expansion of agricultural institutes throughout the country, agricultural education is still an underrated subject in comparison to other fields. There is limited information available about the current status of the agricultural education system in Nepal; in fact, the secondary-level graduates lack proper information and guidance related to higher education in agriculture. This paper explores the history of agricultural education in Nepal; trend of agricultural institutional development; quota distribution, eligibility criteria and admission procedures for undergraduate studies in different universities; and has been prepared with a motive to shed light on agricultural academics, and guide students who are seeking a bright future in the agriculture sector.